1984
DOI: 10.1002/pol.1984.180221102
|View full text |Cite
|
Sign up to set email alerts
|

Miscible blends of amorphous polymers

Abstract: Thirty‐five polymethacrylate/chlorinated polymer blends were investigated by differential scanning calorimetry. Poly(ethyl), poly(n‐propyl), poly(n‐butyl), and poly(n‐amyl methacrylate)s were found to be miscible with poly(vinyl chloride) (PVC), chlorinated PVC, and Saran, but immiscible with a chlorinated polyethylene containing 48% chlorine. Poly(methyl) (PMMA), poly(n‐hexyl) (PHMA), and poly(n‐lauryl methacrylate)s were found to be immiscible with the same chlorinated polymers, except the PMMA/PVC, PMMA/Sar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Tremblay and Prud'homme 23 examined the miscibility of blends of alkyl polymethacrylates with chlorinated polymers (including PVC, CPE, and CPVC) and found that a high chlorine content of the chlorinated polymer (48-56wt% Cl) and an optimum CH 2 /COO ratio in the polymethacrylate were required to obtain miscibility. However, CPE, PVC, and CPVC all have different sequence distributions of CH 2 and CHCl; thus these polymers can be expected to display different miscibility behaviors when blended with PMMA.…”
mentioning
confidence: 99%
“…Tremblay and Prud'homme 23 examined the miscibility of blends of alkyl polymethacrylates with chlorinated polymers (including PVC, CPE, and CPVC) and found that a high chlorine content of the chlorinated polymer (48-56wt% Cl) and an optimum CH 2 /COO ratio in the polymethacrylate were required to obtain miscibility. However, CPE, PVC, and CPVC all have different sequence distributions of CH 2 and CHCl; thus these polymers can be expected to display different miscibility behaviors when blended with PMMA.…”
mentioning
confidence: 99%
“…If the cloud point values are taken to be a qualitative indication of the strength of interactions [21,22], halogen-containing polymethacrylates then interact more strongly with poly(alkyl methacrylate)s than with poly(alkyl acrylate)s. Low cloud-point values of blends of PVC with poly(alkyl acrylate)s and copolyacrylates have been reported [23]. The poorer miscibility of poly(alkyl acrylate)s as compared with poly(alkyl methacrylate)s has been attributed to the self-association of poly(alkyl acrylate)s involving the ␣-hydrogen and carboxyl groups [4].…”
Section: Discussionmentioning
confidence: 97%
“…Tremblay and Prud'homme [4] found that an optimum CH 2 /COO ratio of the poly(alkyl methacrylate) is required to achieve miscibility with chlorinated polymers. Walsh and Sham [23] found that the cloud points of blends of PVC with poly(alkyl acrylate)s or copolyacrylates are a function of carbonyl content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When PMMA content exceeded 60 wt%, the system became heterogeneous. Differential scanning calorimetry (DSC) results 5 reported by Tremblay et al showed that PVC is miscible with PMMA in the range of PVC content up to 54%. The miscibility of PVC with ethyleneethyl acrylate--carbon monoxide terpolymers was studied by Robeson et al 6 by means of dynamic mechanical measurements.…”
mentioning
confidence: 98%